Analisis Akuntabilitas Birokrasi Publik Dalam Sistem Keuangan Dareah Dan Dampaknya Terhadap Kinerja Pelayanan Publik - Lathifah, Hilma; Frinaldi, Aldri; Asnil, Asnil; Putri, Nora Eka (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research aims to analyze the role of participatory accountability in regional financial reform, especially in encouraging community involvement in regional budget oversight. Regional financial reform in Indonesia is focused on increasing transparency and accountability through the application of digital technology such as e-budgeting, e-audit, and the Regional Financial Information System (SIKD). Active community participation, both directly and indirectly, is an important element in ensuring effective and efficient use of the budget. This research uses qualitative methods with a case study approach in several regions that have implemented community participation in APBD supervision. The research results show that community involvement can increase financial transparency and encourage accountability of public officials, but there are obstacles such as a lack of public communication space and digital literacy. To overcome these obstacles, policies are needed that support more inclusive community involvement and wider application of information technology. Thus, the integration of participatory accountability and digitalization of regional finance is expected to strengthen more transparent and accountable financial governance, as well as increase public trust in regional governments. This research contributes to the development of regional financial policies that are oriented towards transparency and community participation.